Corrigendum / Erratum / Retraction - Bhuwana, I.P.A.; Budasi, I.G.; Mahendrayana, G. (Universitas Pendidikan Ganesha, 2018)
RETRACTION TO:Bhuwana, I.P.A., Budasi, I.G., Mahendrayana, G. (2018). Analysis of Slang Words Formation Found in the Lyrics of Drake’s Songs. Language and Education Journal Undiksha, 1(2), 71-79, DOI: http://dx.doi.org/10.23887/leju.v1i2.20258. This article has been retracted by Publisher based on the following reason: Requested by Author by mail at July, 14th 2018.The author informed that he has sent the similar article to other journal that made he wanted to retract the article that was published in Language and Education Journal Undiksha in ordered to avoid the similar article published in two different journals. Editor checked the article and then decided to retract it from Language and Education Journal Undiksha in ordered to avoid published the similar article from other journal.